2015
DOI: 10.4314/bcse.v29i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amino acids and protein content in fresh and commercial royal jelly from Bulgaria

Abstract: ABSTRACT. Royal jelly (RJ) is popular among consumers around the world due to its perceived health benefits. The purpose of this study was to assess the levels of free and total amino acid profile as well as protein content in order to characterize Bulgarian RJ samples. A total of 17 fresh and commercial RJ samples from different regions of Bulgaria were analyzed. The results obtained show that proline (Pro), lysine (Lys), methionine (Met), aspartic acid (Asp), cysteine (Cys), histidine (His) were major free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Samples from different regions of Bulgaria were tested and similar results to those reported by Pavel et al 24 were found. Balkanska et al 25 reported mean protein values of 16.1% and 13.2%. In the present study, the lowest protein content was observed in powder samples.…”
Section: Protein Contentmentioning
confidence: 97%
“…Samples from different regions of Bulgaria were tested and similar results to those reported by Pavel et al 24 were found. Balkanska et al 25 reported mean protein values of 16.1% and 13.2%. In the present study, the lowest protein content was observed in powder samples.…”
Section: Protein Contentmentioning
confidence: 97%
“…RJ is naturally non-homogeneous, and reported findings refer to many samples, locations, production and methods of sampling and analysis used. The analysis of samples from different geographical origins have shown that environmental conditions do not significantly influence the main components Popesco et al, 2008;Balkanska, Zhelyazkova, & Ignatova, 2012). As all foods of animal origin, RJ could be contaminated with antibiotic or pesticide residues (Zhang et al, 2012).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Royal jelly (RJ) is secreted by the hypopharyngeal and mandibular glands of worker honeybees (Apis mellifera) (Balkanska, Zhelyazkova, & Ignatova, 2012). This secretion is produced in worker bees' stomach due to the incomplete digestion of honeydew (Moselhy, Fawzy, & Kamel, 2013;Melliou & Chinou, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work carried out by different researchers reported that the amino acid balance of the food consumed by the honey bees can influence the amino acid composition of the RJ (Balkanska and Zhelyazkova, 2015;Jie et al, 2016), it could be assumed that by feeding honey bees with a protein source that has the amino acids responsible for antihypertensive activity, an RJ that helps a better control BP will be obtained. The objective of this study was to evaluate the effect of different protein sources in the diets of bees and how it affects the amino acid profile of the royal jellies produced, as well as the antihypertensive activity of these measured trough in vitro and in vivo tests.…”
Section: Introductionmentioning
confidence: 99%